Surpresas do passado e percepções contemporâneas: fotografia, memória e mundo do trabalho - Czamanski, Rafael (2018)
The following study has analyzed the memories and the narratives of retired teachers of the University Universidade de Passo Fundo (UPF). Photographic records obtained during the course of History of the Educational Institute assisted in the act of ‘looking back in History’. Memories and trajectories of these characters were stimulated during their narratives with the help of photos. This way, social and collective perceptions or the elderly while individuals belonging to a social group could be explored. In order to hear the narratives and build a consistent analysis, techniques of oral storytelling were applied. Photographic enhancements followed by guideline topics oriented the interviews with guiding questions; the narratives were interpreted following the concept of collective memory, a theory created by Maurice Halbwacs, an important French sociologist. In their reports, the faculty members shared certain particularities; among them stood out: the employment connections with the entity, the age range, and the retirement stage of these individuals. While promoting a theoretical and multidisciplinary incursion, Photography allowed accessing the memory and social perceptions of the retired teachers. Among the results of the study, it became evident that Photography could be a link between Past and Present, since the faculty members, with the aid of photographic records, recognized themselves as historical subjects and participants of institutional History. The attendees of the research demonstrated feeling, remembrances and memories in their narratives. The use of photos of the Institution contributed so that the interviewed could establish a connection between the collective memory and the work field.